2018
DOI: 10.1002/aur.1982
|View full text |Cite
|
Sign up to set email alerts
|

Heart rate mean and variability as a biomarker for phenotypic variation in preschoolers with autism spectrum disorder

Abstract: Cardiac activity, such as heart rate and heart rate variability, is linked to a wide range of psychological functions. This study shows that there is an association between heart rate and heart rate variability and language skills in young children with autism spectrum disorder (ASD). These results may help us understand what underlies individual differences in developmental abilities in young children with ASD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 59 publications
(78 reference statements)
2
23
1
Order By: Relevance
“…This study aimed to obtain reference values in healthy children for candidate digital endpoints related to physical activity in the form of 90% prediction intervals. While these graphically presented prediction intervals could be used as a screening tool for pediatric patients, individual predictions that take weather condition, wear time and city of residence into account may be more appropriate and can be calculated using the model coefficients in S2 Table. HR has been proposed as a candidate biomarker in, among others, pediatric pulmonology, intensive care and psychiatry [25][26][27], and remote non-invasive HR monitoring could extend this measurement to the home-setting. In the past, Pelizzo et al have shown that HR measured via PPG technology can be reliable in children [28].…”
Section: Plos Onementioning
confidence: 99%
“…This study aimed to obtain reference values in healthy children for candidate digital endpoints related to physical activity in the form of 90% prediction intervals. While these graphically presented prediction intervals could be used as a screening tool for pediatric patients, individual predictions that take weather condition, wear time and city of residence into account may be more appropriate and can be calculated using the model coefficients in S2 Table. HR has been proposed as a candidate biomarker in, among others, pediatric pulmonology, intensive care and psychiatry [25][26][27], and remote non-invasive HR monitoring could extend this measurement to the home-setting. In the past, Pelizzo et al have shown that HR measured via PPG technology can be reliable in children [28].…”
Section: Plos Onementioning
confidence: 99%
“…Finally, as suggested above, recent large scale trials (Bazelmans et al, 2018), and systematic reviews (Klusek et al, 2015; Lydon et al, 2016) of the literature on physiological reactivity to sensory, social, and emotional stimuli indicate that differences in cardiovascular arousal exist for many individuals with ASD.…”
Section: Introductionmentioning
confidence: 81%
“…For both the baseline and experimental task recording, four participants from the 52 who completed the direct assessments had no usable ECG data due to electrode refusal (n=2) and corrupted data les (n=2). For the baseline recording, ECG segments with more than three consecutive missing peaks or 10% of data missing were excluded (as in previous studies of autistic populations) (37), and participants with ≥ 50% missing task data overall were excluded (n=4), leaving a nal sample of n=44 for the baseline HR data. For the experimental task, ECG task segments with more than one peak missing were excluded, and as before, participants with ≥ 50% missing task data were excluded (n=1), leaving a nal sample of n=47 for the frustration task HR data.…”
Section: Physiological Data Extraction and Processingmentioning
confidence: 99%